Exploring intimate partner violence in the relationships of adolescents and young adults - Sidhu, M. (2018)
Although the issue of intimate partner violence (IPV) has received much attention, this has largely focused on adult relationships despite recent findings indicating that IPV is also a substantial problem in adolescent and young adult (AYA) relationships. Particularly, there has been little research conducted in the UK. The thesis followed a developmental pathway with each chapter mapping onto a different stage of development from early childhood to young adulthood. The thesis began with a case study that explored and mapped IPV with a specific individual and how her early experiences and attachment difficulties presented later in her intimate relationships. Specifically, the case study highlighted the client’s insecure anxious attachment style appeared to underpin her pattern of forming intimate relationships where she was at risk of being victimized, and later of perpetrating abuse. The importance of early environments and familial risk factors was then focused on in greater detail in the systematic review. The review highlighted that children who had been maltreated and those who were exposed to parental violence were at greater risk of being victims of IPV when they were older. Social learning theory was utilised as an approach to understand this as individuals may normalise aggressive behaviours they are exposed to as a child, leading to them becoming entrenched patterns of dealing with their own conflict as they grow up. The findings from the systematic review also highlighted the need to utilise a measure of conflict that was developed and validated with AYA, which was the focus of chapter 3 and in doing so moved further into the developmental pathway by focusing on adolescent conflict behaviours specifically. Finally, the research study looked at factors and prevalence rates involved in the re-victimization of IPV in AYA aged 16-24. Prevalence of emotional violence was highest, being endorsed by 40% of the study cohort. When focusing on re-victimization, it was found that coping style was not a predictor of IPV re-victimization in the current study population, although attitude to IPV and having a partner who utilised aggressive methods to deal with conflict were predictors. In conclusion, the findings provide greater context to AYA IPV in the UK, however early intervention work looking specifically at emotional violence and attitudes to IPV should be focused on in order to reduce the risk of re-victimization into young adulthood.